Natural history and current state of knowledge of the ducks in Mexico: threats and conservation (Biocenosis, 2024)
Ducks have a wide natural distribution and are a diverse group in morphology and behavior. However, these birds are subject to strong environmental and human pressures, which threaten their permanence, without considering that they fulfill important ecological functions such as regulating populations of invertebrates and aquatic weeds, seed dispersal, improving water quality, among others. For this reason, in this document a literature review was carried out in specialized databases to describe the current state of knowledge of ducks in Mexico, information was collected regarding biology and ecology published until the year 2023. Each publication was classified into 16 topics to determine the state of knowledge and detect information gaps. Despite being a common, diverse group of birds, widely distributed throughout the country and of great ecological and socioeconomic importance, studies on its ecology are very scarce (n=100), with distribution patterns among the most studied. The conservation of aquatic environments and the regulation of human activities are key elements to maintain biodiversity and healthy aquatic ecosystems. This will allow us to establish priorities for research and conservation purposes for this group of birds.
Keywords: Anatidae; birds; biodiversity; conservation; wetlands